SYNTHESIS OF 3D MRI BRAIN IMAGES WITH SHAPE AND TEXTURE GENERATIVE ADVERSARIAL DEEP NEURAL NETWORKS - CHONG, CHEE KEONG (2021)
Generative Adversarial Network (GAN) is emerging as an exciting training paradigm which promises a step improvement to the impressive feature learning capabilities of deep neural networks.